Respostas

2014-07-21T14:32:27-03:00
6x=33-3y          x=33-3y/6                                                                                   6(33-3y/6)         corta-se o 6                                                                               33-3y=0                                                                                                             -3y=-33*(-1)                                                                                                       3y=33                                                                                                                y=33/3                                                                                                               y=11              logo,x=0 e y=11